Enhancing cycling performance using an eccentric chainring - Hue, O.; Galy, O.; Hertogh, C.; Casties, J. F.; Prefaut, C. (Medicine & Science in Sports & Exercise, 2001)
Purpose and Methods: This study was designed to compare the physiological responses and performance of well trained cyclists riding with two different chainring designs, round or eccentric, during a brief and intense cycling exercise: an "all-out" 1-km laboratory test. The eccentrically designed chainring was made of two crank arms sliding into each other, with the inside arm fixed on the center of the arm of a circular chainring and the outside arm sliding along the inside and revolving around an elliptical cam. This design increases crank arm length at the downstroke and decreases it during the upstroke, thus increasing and decreasing the torque. In terms of the chainring's revolution, the crank arm length at 0 degrees and 180 degrees is similar to the arm length of circular chainrings (175 mm). However, during the downstroke (0-180 degrees ), it increases to its maximum length of 200 mm at 90 degrees and then returns to its original length of 175 mm at 180 degrees. During the upstroke, it decreases to a minimum length of 150 mm at 270 degrees and then increases to 175 mm at 360 degrees. Eleven cyclists performed an all-out 1-km laboratory test using each chainring. The study was conducted over two consecutive weeks with the order of chainring use randomized. During all trials, ventilatory data were collected every minute using an automated breath-by-breath system. Heart rate was measured using a telemetry system. Results: None of the cardiorespiratory variables showed significant differences between chainring trials. Performance, however, was significantly improved using the eccentric design (64.25 +/- 1.05 vs 69.08 +/- 1.38 s, P < 0.004, with the eccentric and the round design, respectively). Conclusion: We concluded that the eccentric chainring significantly improved the cycling performance during an all-out 1-km test. Further testing with indoor cycling specialists performing on a velodrome would be helpful to define the maximal possibilities of such a chainring.